Resistant starch and arabinoxylan augment SCFA absorption, but affect postprandial glucose and insulin responses differently. Issue 9 (14th May 2014) - Ingerslev, Anne Krog; Theil, Peter Kappel; Hedemann, Mette Skou; Lærke, Helle Nygaard; Bach Knudsen, Knud Erik
<x content-type="archive" xml:space="preserve">Abstract</x> The effects of increased colonic fermentation of dietary fibres (DF) on the net portal flux (NPF) of carbohydrate-derived metabolites (glucose, SCFA and, especially, butyrate), hormones (insulin, C-peptide, glucagon-like peptide 1 and glucose-dependent insulinotropic peptide) and NEFA were studied in a healthy catheterised pig model. A total of six pigs weighing 59 (sem 1·6) kg were fitted with catheters in the mesenteric artery and in the portal and hepatic veins, and a flow probe around the portal vein, and included in a double 3 × 3 cross-over design with three daily feedings (at 09.00, 14.00 and 19.00 hours). Fasting and 5 h postprandial blood samples were collected after 7 d adaptation to each diet. The pigs were fed a low-DF Western-style control diet (WSD) and two high-DF diets (an arabinoxylan-enriched diet (AXD) and a resistant starch-enriched diet (RSD)). The NPF of insulin was lower (P= 0·04) in AXD-fed pigs (4·6 nmol/h) than in RSD-fed pigs (10·5 nmol/h), despite the lowest NPF of glucose being observed in RSD-fed pigs (203 mmol/h, P= 0·02). The NPF of total SCFA, acetate, propionate and butyrate were high, intermediate and low (P< 0·01) in AXD-, RSD- and WSD-fed pigs, respectively, with the largest relative increase being observed for butyrate in response to arabinoxylan supplementation. In conclusion, the RSD and AXD had different effects on the NPF of insulin and glucose, suggesting different impacts of arabinoxylan and resistant starch on human health.